Evaluation of lift-off effect on surface defect metal with non non-conductive coating by using eddy current testing technique - Syafiqa Putri Adlina Harun (2023)
Eddy Current Testing (ECT) technique is a Non-Destructive Testing (NDT) method widely used in industries. The advantages of using the Eddy Current Testing technique are highly capable of detecting surface defects, determining material properties, e.g., conductivity and electrical permeability, measuring the thickness of materials, and performing nonconductive coatings on metal testing. However, the main obstacle of ECT is difficulty in detecting deeper defects and the undesirable lift-off distance between the sample and the sensor. Moreover, when applying the eddy current testing approach, nonmagnetic coating thickness variation frequently impedes flaw detection in metal testing. This research aims to develop the eddy current testing probe that generates eddy current signals when a coil is placed above each metal testing, i.e., copper 101, aluminium 6061, and stainless steel 304, with and without nonconductive coating and the presence of lift-off height, i.e., 0 mm, 2.5 mm, 5.0mm, 7.5 mm, and 10.0 mm. In addition, each metal test has a variety of thicknesses, i.e., 1.5 mm, 3.0 mm, and 5.0 mm, and an artificial surface defect, i.e., 10 mm, 20 mm, and 30 mm, engraved on each metal testing. The coil probe is a rod-shaped solenoid coil designed with an iron core with 65 mm length, 5 mm area, and 200 N turns. It demonstrates how the rod-shaped solenoid coil may be used to detect various surface defects in copper 101 (C101), aluminium 6061 (Al6061), and stainless steel 304 (SS304). The optimal frequencies for C101 were 7.850 MHz, aluminium Al6061was 7.383 MHz, and SS304 metal was 7.956 MHz. In conclusion, the output voltage signals for larger surface defect sizes increase but decrease as the thickness becomes thicker. Furthermore, as the lift-off height increases, the output voltage for both coated and non-coated metal decreases accordingly. Therefore, besides comparing the output voltage for coated and non-coated metals, there are minor differences which shows that the ECT technique in this research can still detect surface defects appropriately.